Relaxing Melody from Flute Combined with a Foot Massage Can Reduce Systolic and Diastolic Blood Pressure in Elders (Medico Legal Update, 2019)
Background: Hypertension in elders is affected by physiological changes in the structure and cardiovascularfunctions. One alternative of non-pharmacological treatment for hypertension is the combination of footmassage and harp-flute (kecapi suling) music therapies, which can give a relaxing sensation in the bloodpressure.Objective: This study aims to observe the effect of the combination of foot massage and kecapi suling musictherapies against systolic and diastolic blood pressure.Method: This research uses the pre-experimental design (one group pretest-posttest design). The populationwas elders with hypertension in Werdha Hargo Dedali Nursing Home in Surabaya. Purposive samplingtechnique was used to obtain 14 respondents. The independent variables were foot massage and kecapisuling music therapies, whereas the dependent variable was the blood pressure reduction. The data wereanalyzed by using Paired-Samples T-Test with significance value ?0.05.Results: The study indicated that the combination of foot massage and kecapi suling music therapies affectedsystolic and diastolic blood pressure reduction in elders with hypertension. The systolic blood pressureaverage value in the pre-intervention was 154.64 mmHg, while the average value in the post-interventionwas 138.86 mmHg. Diastolic blood pressure average value in the pre-intervention was 92.21 mmHg, whilethe average value in the post-intervention was 88.00 mmHg.Conclusion: There is an effect of the combination of foot massage and kecapi suling music therapies ondecreasing blood pressure in elders with hypertension. The decrease in systolic blood pressure occurred inall respondents, while not all respondents experienced diastolic blood pressure declin